2016
DOI: 10.1016/j.reprotox.2016.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine and caffeinated beverage consumption and fecundability in a preconception cohort

Abstract: Caffeine is an adenosine receptor antagonist that may influence fertility by affecting ovulation, menstrual characteristics, or sperm quality. We studied the association between female and male preconception caffeine intake and fecundability in a North American prospective cohort study of 2,135 pregnancy planners. Frequency of caffeinated beverage intake was self-reported at baseline. Outcome data were updated every 8 weeks until reported pregnancy; censoring occurred at 12 months. Adjusted fecundability ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 39 publications
2
51
0
Order By: Relevance
“…Specifically, among 3628 women planning a pregnancy in Denmark the adjusted fecundability ratios were 0.89 (0.80–0.98), 0.85 (0.71–1.02), 0.84 (0.57–1.25), and 0.48 (0.21–1.13) for < 1, 1, 2, and 3+ servings per day, respectively, compared with none (16). This inverse association with fecundity, however, was not confirmed in a more recent prospective study among 2135 North American pregnancy planners (11). Moreover, in this same cohort of women, there was no link between pre-pregnancy soda consumption and pregnancy loss (35).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Specifically, among 3628 women planning a pregnancy in Denmark the adjusted fecundability ratios were 0.89 (0.80–0.98), 0.85 (0.71–1.02), 0.84 (0.57–1.25), and 0.48 (0.21–1.13) for < 1, 1, 2, and 3+ servings per day, respectively, compared with none (16). This inverse association with fecundity, however, was not confirmed in a more recent prospective study among 2135 North American pregnancy planners (11). Moreover, in this same cohort of women, there was no link between pre-pregnancy soda consumption and pregnancy loss (35).…”
Section: Discussionmentioning
confidence: 81%
“…Insulin resistance is a situation in which the responsiveness of the body to the hormone insulin is diminished, resulting in metabolic dysregulation (30, 31). Insulin resistance can alter the maternal metabolic environment and follicular fluid microenvironment, leading to lower quality oocytes and embryos (9, 11, 32). In mice, this condition leads to altered mitochondrial function and abnormal spindle formation (33).…”
Section: Discussionmentioning
confidence: 99%
“…Any damage to Sertoli cells will result in a decrease of inhibin B and an increase in the levels of FSH [25,26], both hormones that might help to determine the mechanisms of action of energy drinks in further studies. Interestingly, in a preconception cohort, a recent study showed that caffeinated soda and energy drink intake were associated with reduced fecundability among males, but not among females [27]. Testosterone levels did not show any difference between the control and treated groups (Table 2).…”
Section: Discussionmentioning
confidence: 87%
“…The reason for paternal strong tea drinking increasing the risk of NSCL/P might be attributed to caffeine, which was a plant alkaloid in teas. Evidences from both animal experiments and human studies [3840] demonstrated that the intake of caffeine and caffeinated beverages among males could impair reproductive organs, sperm characteristics, and sperm quality, affect fertility and fetal health, and even cause birth defects. Eight predictors selected by a discriminant analysis were with good representativeness and availability.…”
Section: Discussionmentioning
confidence: 99%